Using Objective, Real-Time Measures to Investigate the Effect of Actual Physical Activity on Affective States in Everyday Life Differentiating the Contexts of Working and Leisure Time in a Sample with Students - Kanning, Martina K. (Frontiers in Psychology, 2013)
Multiple studies suggest that physical activity causes positive affective reactions and reduces depressive mood. However, studies and interventions focused mostly on structured activity programs, but rarely on actual physical activity (aPA) in daily life. Furthermore, they seldom account for the context in which the aPA occur (e.g. work, leisure). Using a prospective, real time assessment design (ambulatory assessment), we investigated the effects of aPA on affective states (valence, energetic arousal, calmness) in real time during everyday life while controlling for the context. 87 undergraduates students (Age: M = 24.6; SD = 3.2, females: 54%) participated in this study. aPA was assessed through accelerometers during 24-hours. Palmtop devices prompted subjects approximately every 45 minutes during a 14-hour daytime period to assess their affective states and the context. We analyzed within- and between-person effects with hierarchical modeling (HLM 6.0). Multilevel analyses revealed that both aPA and context influenced subsequent affective states. The interaction of aPA and context did predict energetic arousal only. State levels of affects did not differ between men and women. For both men and women, aPA in everyday life has an effect on individual’s affective states. For valence and calmness, it seems to be independent of the context in which the aPA occur. For energetic arousal, men reported to have lower feelings of energy and women reported to have more feelings of energy during leisure time compared to working episodes.